2023
DOI: 10.1109/access.2023.3267737
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Software Defined Content Delivery Network: A Novel Combination of CDN and SDN

Abstract: With the rapid growth of multimedia services, the burden of infrastructure is becoming heavier, which may not guarantee a high-quality experience for users. Whether the multimedia category is video on demand (VOD), live broadcast, or social media is a hot issue. Traditionally, content delivery network (CDN) service providers deploy servers as close to clients as possible to reduce latency. CDN is an overlay network mainly responsible for routing requests, distribution, delivery, and audit. As a supplement to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 124 publications
0
1
0
Order By: Relevance
“…In a research article [28], the authors compared different load-balancing techniques to determine the research gap for increasing QoS in telecom networks. In a research article [29], the authors combined a content delivery network (CDN) and SDN to enhance the quality of the network. In a research article [30], the authors suggested a traditional round ribbon technique for maximizing the availability of servers.…”
mentioning
confidence: 99%
“…In a research article [28], the authors compared different load-balancing techniques to determine the research gap for increasing QoS in telecom networks. In a research article [29], the authors combined a content delivery network (CDN) and SDN to enhance the quality of the network. In a research article [30], the authors suggested a traditional round ribbon technique for maximizing the availability of servers.…”
mentioning
confidence: 99%